Developing writing skills among students with learning disabilities in English language - Mohamad Ahmad Saleem Khasawneh; Eman Khaled Tawafiq Alatoom (Journal of Social Studies (JSS), 2022)
This study explored the effect of active learning on developing writing skills among students with learning disabilities in English language in Irbid, Jordan. The sample of the study included (40) male and female students, who were selected purposefully, and distributed randomly into two groups. The first was one the experimental group that was taught using the active learning method, and the other was the control group that was taught according to the traditional method. The study used the writing test after checking its validity by presenting it to a group of arbitrators, and its reliability by the method of testing and re-testing using the Pearson coefficient, which was (0.90). The results of the study showed that there were clear differences between the scores of the two study groups on the post-writing test. In light of the findings of the study, the researcher recommended training educational supervisors and teachers on practical applications of using the active learning method and evaluating it in the classroom through seminars and workshops in this field.